2009
DOI: 10.1186/1471-213x-9-27
|View full text |Cite
|
Sign up to set email alerts
|

Mouse H6 Homeobox 1 (Hmx1) mutations cause cranial abnormalities and reduced body mass

Abstract: Background: The H6 homeobox genes Hmx1, Hmx2, and Hmx3 (also known as Nkx5-3; Nkx5-2 and Nkx5-1, respectively), compose a family within the NKL subclass of the ANTP class of homeobox genes. Hmx gene family expression is mostly limited to sensory organs, branchial (pharyngeal) arches, and the rostral part of the central nervous system. Targeted mutation of either Hmx2 or Hmx3 in mice disrupts the vestibular system. These tandemly duplicated genes have functional overlap as indicated by the loss of the entire ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
48
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(54 citation statements)
references
References 22 publications
5
48
0
Order By: Relevance
“…Mendelian transmission of the dumbo allele was observed between embryonic day (E) 10.5 and E14.5 (42 Hmx1 +/+ , 105 Hmx1 +/dm and 37 Hmx1 dm/dm embryos; χ 2 P=0.1391). However, similar to the previous study on a mixed genetic background (Munroe et al, 2009) mice (31.4%, 55.1% and 13.5%, respectively; χ 2 P=0.0029), suggesting ∼57% perinatal lethality of homozygous mutants, which appeared to be equally distributed between the sexes. In contrast to the earlier report (Munroe et al, 2009), only postweaning Hmx1 dm/dm male mice showed a significant reduction in weight, on average ∼23% lighter than controls (control: 17.28± 0.494 g, Hmx1 dm/dm : 13.29±1.102 g).…”
Section: Hmx1 Mutant Mice Exhibit Craniofacial and Cranioskeletal Anosupporting
confidence: 64%
See 4 more Smart Citations
“…Mendelian transmission of the dumbo allele was observed between embryonic day (E) 10.5 and E14.5 (42 Hmx1 +/+ , 105 Hmx1 +/dm and 37 Hmx1 dm/dm embryos; χ 2 P=0.1391). However, similar to the previous study on a mixed genetic background (Munroe et al, 2009) mice (31.4%, 55.1% and 13.5%, respectively; χ 2 P=0.0029), suggesting ∼57% perinatal lethality of homozygous mutants, which appeared to be equally distributed between the sexes. In contrast to the earlier report (Munroe et al, 2009), only postweaning Hmx1 dm/dm male mice showed a significant reduction in weight, on average ∼23% lighter than controls (control: 17.28± 0.494 g, Hmx1 dm/dm : 13.29±1.102 g).…”
Section: Hmx1 Mutant Mice Exhibit Craniofacial and Cranioskeletal Anosupporting
confidence: 64%
“…S1A-D′). This may represent a mild neural tube defect related to the exencephaly previously documented on the mixed background (Munroe et al, 2009) and might contribute to the occasional perinatal lethality of homozygous mutant embryos.…”
Section: Hmx1 Mutant Mice Exhibit Craniofacial and Cranioskeletal Anomentioning
confidence: 99%
See 3 more Smart Citations